Relevansi Berhijab Terhadap Pembentukan Perilaku Muslimah - Mahmud Rifaannudin; Anisa Salsabila Rahmah (Universitas Darussalam Gontor, 2023)
Islam is a religion that glorifies women, by looking the importance of women's role in life. Islam is also a universal religion so that it does not only regulate the relationship of a servant with his God but also with fellow human beings. The command to wear the hijab is not limited to the obedience of a servant, but by wearing the hijab, she protects herself and those around her from the bad things that might happen. By wearing the hijab, someone is indirectly encouraged to pay attention to and improve their behavior, because the hijab serves as their identity as a Muslim woman and is a form of obedience to Allah's commands, so that their behavior will be noticed by others, maybe even emulated. However, there is a problem where many Muslim women who already wear the hijab do not understand the meaning, the purpose and the wisdom behind the mandatory on the hijab so that the hijab is worn only because it is requirement, or even a trend. Then those who reject the hijab use the excuse that what is more important is improving morals, not covering the aurat with the hijab. So this study aims to provide an explanation of the hijab, its meaning, its purpose and its wisdom behind its stipulations, as well as provide solutions so that Muslim women can slowly improve themselves after committing to wearing the hijab. The method used in this study is qualitative, with a descriptive-analytical presentation. After studying the verses that make it mandatory to wear the hijab, it can be seen that the hijab has a meaning “to cover”, and aims to protect Muslim women from disturbances, and encourage Muslim women to maintain their behavior because hijab is also an Islamic identity and the obedience of a Muslim woman. So there should be no conflict between the noble character and obedience to cover the aurat.